30th anniversary in Vytautas Magnum university of Romas Kalanta selfburn - Streikus, Arūnas (Genocidas ir rezistencija, 2002)
The 30th anniversary of self-immolation of Romas Kalanta was commemorated by hosting various events. The scientific conference titled Kaunas in 1972: Alternative Culture, Political Protest and Cultural Resistance organised by the History Department of the Faculty of Humanities of Vytautas Magnus University demonstrated an academic ambition to commemorate the sacrifice of Romas Kalanta. The title of the conference lists the contextual phenomena which the organisers believed led to the events of May 1972 in Kaunas, so it was to be expected that they would be the focus of the conference. Thirteen papers presented at the conference can be broken down into three categories: 1) papers dedicated to the various aspects of Kalanta’s self-immolation and related events; 2) papers analysing the repercussions and impact of these events; and 3) papers discussing the broader context of the events of May 1972.